The genus Hebeloma in the Rocky Mountain Alpine Zone - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (MycoKeys, 2019)
Numerous taxa of Hebeloma have been reported in association with Salix, Dryas, and Betula in arctic-alpine habitats. However, species are notoriously difficult to delineate because morphological features overlap, and previously there was little reliable molecular data available. Recent progress in ITS-sequencing within the genus, coupled with an extensive database of parametrically described collections, now allows comparisons between species and their distributions. Here we report 16 species of Hebeloma from the Rocky Mountain alpine zone from some of the lowest latitudes (latitude 36°–45°N) and highest elevations (3000–4000 m) for arctic-alpine fungi in the northern hemisphere. Twelve of these species have been reported from arctic-alpine habitats in Europe and Greenland and are now molecularly confirmed from the Middle and Southern Rockies, greatly expanding their distribution. These are: Hebeloma alpinum, H. aurantioumbrinum, H. dunense, H. hiemale, H. marginatulum, H. mesophaeum, H. nigellum, H. oreophilum, H. subconcolor, H. spetsbergense, H. vaccinum, and H. velutipes. Hebeloma hygrophilum is known from subalpine habitats in Europe, but was never recorded in arctic-alpine ecology. Three species recorded from the Rockies, but as yet not reported from Europe, are H. alpinicola, H. avellaneum, and H. excedens. The last two have never previously been reported from an arctic-alpine habitat. For all three of these species, the holotypes have been studied morphologically and molecularly, and have been incorporated into the analysis.